STRUCTURE OF MORPHOLOGICAL CHANGES OF MYOCARDIUM IN NON-CORONARY ORIGIN SYSTOLIC DYSFUNCTION OF THE LEFT VENTRICLE - M. R. Bakhchoyan; E. D. Kosmacheva; A. A. Slavinsky; E. A. Terman; V. A. Porkhanov (Российский кардиологический журнал)
Aim. To assess morphological changes of myocardium in patients with noncoronarogenic systolic dysfunction of the left ventricle (LV).Material and methods. Totally, 96 patients studied. Among the 80 males, 16 females at the age 14-66 y. o. Follow-up duration: April, 2010 — August, 2014. In 81 patient coronary arteriography was done to rule out atherosclerotic lesion of arteries. Nine patients were excluded due to hemodynamically significant stenoses. Others underwent endomyocardial biopsy of the right ventricle.Results. All patients suffered from various degree CHF (by NYHA): FC I — 2,83%, FC II — 16,9%, FC III — 56,33%, FC IV — 23,94%. By EchoCG the ejection fraction of LV was 20,67±8,10%, by left ventriculography — 21,75±8,94%. The intervention group underwent biopsy of the right ventricle with further qualitative and quantitative study of myocardial infiltrate and its histomorphological assessment. We got following results: definite myocarditis — 1,39%, possible myocarditis — 9,71%, myocarditis cardiosclerosis — 6,94%, non-inflammatory cardiomyopathy — 38,9%, amyloidosis — 1,39%. In 37,5% cases myocardial specimens were of common histological structure, without signs of current inflammation and myocyte necrosis; 4,17% of specimens were non-informative due to lack of amount for assessment.Conclusion. The data obtained in the study makes it possible to define nosological structure of severe systolic dysfunction of the LV of non-coronary origin in Krasnodarsky Region. Taken the absence in Russian Federation of any large scale epidemiological studies of the problem, it is necessary to elaborate database and to implement it into routine practice of cardiologists. Such data might improve diagnostics, etiotropic and pathogenetic therapy, and improve outcomes of the diseases group.